European water directive evaluation and decision support system to improve irrigation management: RISP-IDRIC Project - Rinaldi M.; Ruggieri S.; Marcucci C.; Loreti F.; Acutis M.; Malagoli C. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
The recent reform of the Common Agricultural Policy is oriented towards an ecologically-sound agriculture and to a reasonable use of the production factors (technical features, including water). In this context, the Water Directive n. 60/2000 introduces in the water resources management new principles such as polluter pays, the full cost and volumetric pricing. Implementation of the directive could have important effects on the agricultural sector and management. The Consorzio della Bonificazione Umbra, authority, located in Central Italy, is responsible for soil reclamation and conservation, protection of land and the environment, with special reference to water resources for the improvement and transformation of production systems. The RISP-IDRIC is a research project, funded by Italian Ministry of Agricultural (2007-2010) and it will achieve two main goals: (i) To find the most efficient solutions (and less expensive) to meet the targets set by European Water Directive n. 60/2000, giving a methodological support for application of national and regional water directives, testing the impact of different scenarios of contributory systems, consortia remediation and, consequently, agricultural system. (ii) To develop a web irrigation decision system to improve the efficiency of irrigation technology, streamline procedures for irrigation and optimization of the use of water resources, providing specific guidance to farmers for irrigation supply (time and amount) offering them a tool that exploits the advantages of new technologies.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)